Fatty acid metabolism-derived prognostic model for lung adenocarcinoma: unraveling the link to survival and immune response - Wu, Rui-Ze; Sun, Qian-Qian; Fu, Yao; Yu, Han-Nong; Liu, Wei-Yang; Wu, Yong-Hui; Zhang, Han; Pan, Yu-Lin; Rui, Xin (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is one of the most common malignant tumors globally, characterized by poor prognosis and high mortality. Abnormal fatty acid metabolism plays a crucial role in LUAD progression. This study aims to develop a prognostic model based on fatty acid metabolism to improve the overall prognosis of LUAD.Materials and methodsBioinformatics analyses were performed using TCGA and GEO datasets, supplemented by cell experiments. A total of 309 fatty acid metabolism-related genes were identified from MsigDB. Differentially expressed genes were analyzed using the ‘limma’ R package. A prognostic model was constructed using LASSO regression and validated with survival analyses via the ‘survminer’, ‘survival’, and ‘pROC’ R packages. The analysis included somatic mutations, tumor mutation burden, clinical correlations, stemness analysis, cytokine correlations, and enrichment analysis. Protein interaction networks were constructed using STRING and Cytoscape, while immune cell infiltration and immunotherapy responses were evaluated with the ‘oncoPredict’ R package. Results were validated through cell experiments and immunohistochemistry staining of lung tissues.ResultsWe identified 125 differentially expressed genes related to fatty acid metabolism, with 33 genes significantly associated with prognosis. Patients in the high-risk group had poorer overall survival and progression-free survival, and the risk score correlated with gender, N stage, clinical stage, and T stage. The risk score was also associated with cancer stem cells, with a significantly higher mRNAsi index in the high-risk group. Additionally, the risk score correlated with various cytokine expressions and showed significant enrichment in cell cycle pathways. Key genes like CDK1 were highly expressed in LUAD cell lines and validated in clinical samples. The low-risk group showed better responses to immune checkpoint inhibitors, with the risk score correlating with immune checkpoint gene expression.ConclusionThis study successfully established a novel prognostic model based on fatty acid metabolism, which provides valuable insights for the treatment of LUAD.